Risk-Focused Triangulation Audit Model: Analisis Gap Nilai Tercatat dan Nilai Pasar Investasi Saham pada Tiga Emiten BEI Periode 2020-2024 - Tri Koko Apanugra Tri; Fatiyah Sakinah; Taufik Ardiyansah; Anastasya Argiyanti; Eka Merdekawati (STIE PGRI Dewantara Jombang, 2025)
A risk-focused audit framework grounded in evidence triangulation is advanced to enhance the precision of risk assessment and auditor objectivity in evaluating equity investment values. By integrating internal, external, and documentary evidence, the analysis examines the gap between book and market values of three major banking issuers listed on the Indonesia Stock Exchange from 2020 to 2024. The findings reveal substantial disparities that reflect heightened audit risk arising from valuation bias and differing perceptions of economic worth. Evidence triangulation strengthens audit reliability and reframes the auditor’s role from procedural examiner to economic interpreter. Conceptually, the results highlight the strategic integration of accounting information and market evidence as a foundation for risk evaluation, contributing to improved governance, transparency, and accountability within Indonesia’s financial audit practices.